Analysis Of The Role Of Teachers In Improving Learning Motivation Of 5–6-Year-Old Children At Al-Khuzamy Kindergarten In 2024/2025 - Nurhalimah, Nurhalimah; Alawiyah, Tuti; Eliyana, Eliyana (JUPE : Jurnal Pendidikan Mandala, 2025)
Abstract. This study aims to analyze the role of teachers in improving early childhood learning motivation in class B students at Al Khuzamy Menggala Kindergarten in the 2024/2025 academic year with a population of 35 students.The results of this study are: to determine the role of teachers in raising early childhood learning motivation at Al Khuzamy Menggala Kindergarten both in the learning process and outside of learning. The method used is qualitative with data collection techniques in the form of observation, interviews and documentation.Based on the results of the analysis and discussion, it can be concluded that the role of teachers in improving learning motivation at Al Khuzamy Menggala Kindergarten is good. The implementation of the teacher's role in increasing learning motivation is the teacher as a facilitator, the teacher as a director and the teacher as a motivator. To motivate students, teachers usually give praise to students who have done their jobs well, on the other hand, teachers also act wisely in dealing with students who are not disciplined, namely by giving punishment or in the form of reprimands so that students do not neglect their duties and obligations.For obstacles, teachers experience two obstacles, namely limited interaction between teachers and students, an environment that is less supportive. However, from these two obstacles, teachers have tried to increase children's learning motivation.